On adverb formation in Romanian - Daria Protopopescu (Bucharest Working Papers in Linguistics, 2009)
The current paper discusses adverb formation in Romanian starting from the treatment of Spanish –mente adverbs in a recent paper by Torner (2005) who introduces the notion of phrasal affix in his treatment of Spanish –mente adverbs. The analysis of the morphology of Romanian adverbs starts from the three suffixes by means of which the language derives its adverbs (–(a)mente, -(ic)eşte, -iş (-îş)) as well as a bounty of adverbs that have been argued (Forăscu 2002) to be adjectival or participial forms. My proposal is that Romanian (manner) adverbs are derived by means of inflectional affixation, with the above mentioned suffixes, or a silent suffix –Ø – the case of those adverbs that have an identical form to that of the masculine singular adjectives, a suffix that encodes the property (in X manner).